(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Oral administration is the most common drug delivery route with high levels of patient acceptance. However, oral delivery of therapeutic proteins/peptides is extremely difficult, and improving the pharmacological bioavailability still is a challenging goal because of the poor membrane permeability, high molecular weight, and enzymatic degradation of these drugs. Lipid-based nanocarriers represent a viable means for enhancing the oral bioavailability of protein or peptide drugs while minimizing toxicity. Nowadays, like other macromolecules protein or peptide drugs are the promising candidates to be delivered employing liposomes and lipid nanoparticles including solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC). Generally, these drug delivery strategies can reduce protein or peptide drug degradation and improve membrane permeability thus enhance bioavailability. This review demonstrates various lipid-based formulation strategies used for successful oral delivery of peptides and proteins, assesses the hurdles and delivery efficiency and their clinical implications. Dhaka Univ. J. Pharm. Sci. 20(3): 395-416, 2022 (June) Centennial Special Issue